2022
DOI: 10.1200/jco.2022.40.6_suppl.098
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of P-PSMA-101 CAR-T cells in patients with metastatic castration-resistant prostate cancer (mCRPC).

Abstract: 98 Background: P-PSMA-101 is an autologous CAR-T therapy targeting PSMA, with a high percentage of stem cell memory T cells (TSCM) associated with efficacy, safety, and bone homing (particularly relevant to prostate cancer). It is manufactured using a novel non-viral transposon system (piggyBac) that creates high TSCM products. Genes are inserted encoding a PSMA-targeted Centyrin CAR, iCasp9-based safety switch, and DHFR to purify CAR-T cells. P-PSMA-101 completely eliminated tumors in intractable murine mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…There have been five generations of CARs, and their molecular structures and physical properties significantly alter CAR-T cells’ effects in therapeutics [ 46 ]. Currently, PSMA-CAR-T cells (NCT04429451 and NCT04249947), PSCA-CAR-T cells (NCT03873805), and CAR-T-PSMA-TGFβRDN69 cells (NCT03089203 and NCT04227275) are highly effective in mCRPC tested in phase I or phase II clinical trials [ 37 , 47 , 48 , 49 , 50 ]. Natural killer (NK) cells can also be engineered to express the CAR, and recruitment is currently ongoing for an early phase I clinical trial evaluating anti-PSMA CAR-NK cells (NCT03692663) [ 51 ].…”
Section: The Development Of Prostate Cancer Immunotherapymentioning
confidence: 99%
“…There have been five generations of CARs, and their molecular structures and physical properties significantly alter CAR-T cells’ effects in therapeutics [ 46 ]. Currently, PSMA-CAR-T cells (NCT04429451 and NCT04249947), PSCA-CAR-T cells (NCT03873805), and CAR-T-PSMA-TGFβRDN69 cells (NCT03089203 and NCT04227275) are highly effective in mCRPC tested in phase I or phase II clinical trials [ 37 , 47 , 48 , 49 , 50 ]. Natural killer (NK) cells can also be engineered to express the CAR, and recruitment is currently ongoing for an early phase I clinical trial evaluating anti-PSMA CAR-NK cells (NCT03692663) [ 51 ].…”
Section: The Development Of Prostate Cancer Immunotherapymentioning
confidence: 99%
“…During manufacturing, the genes are inserted in a DHFR selection gene, anti-PSMA centyrin CAR gene and iCASP-9-based safety switch to purify CAR-T cells. They are characterized by a lot of memory stem T cells [ 112 ]. In 2022 GU ASCO data, P-PSMA-101 CAR-T cells demonstrated a significant antitumor effect in patients with mCRPC (clinical trial NCT04249947).…”
Section: Chimeric Antigen Receptor (Car) T-cellsmentioning
confidence: 99%
“…In 2022 GU ASCO data, P-PSMA-101 CAR-T cells demonstrated a significant antitumor effect in patients with mCRPC (clinical trial NCT04249947). Seven of ten heavily pre-treated patients with mCRPC achieved a PSA decrease in the preliminary report [ 112 ]. PSMA-targeting TGF-β-insensitive armored CAR-T cells are designed to overcome the suppressive immune microenvironment of PCa [ 113 , 114 , 115 ].…”
Section: Chimeric Antigen Receptor (Car) T-cellsmentioning
confidence: 99%
“…In contrast, CAR T cell therapies targeting solid tumors have lagged due to additional challenges related to the lack of bona fide tumor-specific antigens, inhospitable tumor microenvironments, and poor trafficking, persistence, and expansion of CAR T cells. Despite the challenges observed in driving effective immune responses toward solid tumors, recent early phase clinic trials investigating CAR T cell therapies targeting PSMA in mCRPC have reported safety and evidence of significant biochemical and radiographic responses 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenges observed in driving effective immune responses toward solid tumors, recent early phase clinic trials investigating CAR T cell therapies targeting PSMA in mCRPC have reported safety and evidence of significant biochemical and radiographic responses 8, 9 . These preliminary results serve to embolden efforts to develop and optimize new CAR T cell therapies for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%